Wind power decreases the need for storage in an interconnected 100% renewable European power sector - Alexander Roth; Wolf-Peter Schill (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
The massive expansion of wind power and solar PV is the primary strategy to reduce greenhouse gas emissions in many countries. Due to their variable generation profiles, power sector flexibility needs to increase. Geographical balancing enabled by electricity grids and temporal flexibility enabled by electricity storage are important options for flexibility. As they interact with each other, we investigate how and why interconnection with neighboring countries reduces storage needs. To do so, we apply a cost-minimizing open-source capacity expansion model to a 100% renewable energy scenario of central Europe. We use a factorization method to disentangle the effect of interconnection on optimal storage through distinct channels: differences in (i) countries' solar PV and wind power capacity factors, (ii) load profiles, as well as (iii) hydropower and bioenergy capacity. Results show that geographical balancing lowers aggregate storage capacities by around 30% in contrast to a similar system without interconnection. We further find that the differences in wind power profiles between countries explain, on average, around 80% of that effect. Differences in solar PV capacity factors, load profiles, or country-specific capacities of hydropower together explain up to 20%. Our analysis improves the understanding of the benefits of geographical balancing for providing flexibility and its drivers.
Keywords: C61; Q42; Q49; 330; variable renewable energy sources; electricity storage; interconnection; numerical optimization; 100% renewable energy